Coherence and cohesion: An analysis of the final project abstracts of the undergraduate students of PGRI Semarang - Suwandi, Suwandi (Indonesian Journal of Applied Linguistics, 2016)
An abstract is the gist of a research report which has the purpose to allow the reader to get the main information without reading the whole document. Since it plays an important role in grasping the information of the whole research report, the writing of the abstract, therefore should be concise and the logical relation among sentences is clear, coherent and cohesive. However, many of the students still find difficulties in making their writing coherent due to their limitation in understanding the cohesive devices and their application in their writing. This article attempts to reveal the coherence of the abstracts of the final project reports of the undergraduate students of PGRI University Semarang, Indonesia. Its objectives are (1) to reveal the micro-level coherence, how each sentence is connected to the other to make logical relations and (2) to discover the macro-level coherence, the right use of cohesive devices like conjunction, reference, substitution or ellipsis so as to make the whole text coherent. Several abstracts of the students’ final projects were selected randomly to be analyzed. Since it is a qualitative research, the data were in the level of words or sentences. The result shows that the abstracts analyzed have not satisfactorily achieved coherence though some cohesive devices like reference, conjunctions, ellipsis which are used to link one sentence to the other. Some grammatical mistakes are also found such as the plural forms, active-passive voice.